2018 Consensus statement on exercise therapy and physical interventions (orthoses, taping and manual therapy) to treat patellofemoral pain: Recommendations from the 5th International Patellofemoral Pain Research Retreat, Gold Coast, Australia, 2017 - Collins, Natalie J.; Barton, Christian J.; Van Middelkoop, Marienke; Callaghan, Michael J.; Rathleff, Michael Skovdal; Vicenzino, Bill T.; Davis, Irene S.; Powers, Christopher M.; Macri, Erin M.; Hart, Harvi F.; De Oliveira Silva, Danilo [UNESP]; Crossley, Kay M. (BMJ, 2018)
Patellofemoral pain affects a large proportion of the population, from adolescents to older adults, and carries a substantial personal and societal burden. An international group of scientists and clinicians meets biennially at the International Patellofemoral Research Retreat to share research findings related to patellofemoral pain conditions and develop consensus statements using best practice methods. This consensus statement, from the 5th International Patellofemoral Research Retreat held in Australia in July 2017, focuses on exercise therapy and physical interventions (eg, orthoses, taping and manual therapy) for patellofemoral pain. Literature searches were conducted to identify new systematic reviews and randomised controlled trials (RCTs) published since the 2016 Consensus Statement. The methodological quality of included systematic reviews and RCTs was graded using AMSTAR and PEDro, respectively. Evidence-based statements were developed from included papers and presented to a panel of 41 patellofemoral pain experts for consensus discussion and voting. Recommendations from the expert panel support the use of exercise therapy (especially the combination of hip-focused and knee-focused exercises), combined interventions and foot orthoses to improve pain and/or function in people with patellofemoral pain. The use of patellofemoral, knee or lumbar mobilisations in isolation, or electrophysical agents, is not recommended. There is uncertainty regarding the use of patellar taping/bracing, acupuncture/dry needling, manual soft tissue techniques, blood flow restriction training and gait retraining in patients with patellofemoral pain. In 2017, we launched the International Patellofemoral Research Network (www.ipfrn.org) to consolidate and grow our patellofemoral research community, facilitate collaboration and disseminate patellofemoral pain knowledge to clinicians and the general public. The 6th International Patellofemoral Research Retreat will be held in Milwaukee, Wisconsin, USA, in October 2019.
Keywords: consensus statement; intervention; knee; knee injuries